2016
DOI: 10.1097/prs.0000000000002791
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endothelial Differentiation Capacities of Human and Rat Adipose-Derived Stem Cells

Abstract: Background: The authors compared the endothelial differentiation capacities of human and rat adipose-derived stem cells to determine whether human adipose-derived stem cells can be a source of endothelial cells clinically. Methods: Human and rat adipose-derived stem cells were harvested and characterized with flow cytometry and trilineage differentiation. Cells from passages III through V were fed with endothelial cell differentiation medium for up to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…ADSCs from passages 3 and 4 were reported to be used in regenerative medicine (13)(14)(15). The results of this study also indicated no significant difference in spontaneous and induced adipogenic differentiation potential between cells of passages 3 and 4.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…ADSCs from passages 3 and 4 were reported to be used in regenerative medicine (13)(14)(15). The results of this study also indicated no significant difference in spontaneous and induced adipogenic differentiation potential between cells of passages 3 and 4.…”
Section: Discussionsupporting
confidence: 59%
“…The spontaneous adipogenic differentiation of ADSCs was assumed to decrease when the cells were passaged serially. ADSCs from passages 3 and 4 were reported to be used in regenerative medicine (13)(14)(15). Krähenbühl et al (16) reported that cell morphology changed and growth slowed down when extended to passages 6 and beyond.…”
Section: Introductionmentioning
confidence: 99%
“…These multipotent cells can be harvested from various tissues, such as adipose tissue, bone marrow, periosteum, and synovium [16][17][18][19] . Owing to their abundant source and easy access, adipose-derived stem cells (ASCs) have become the principal source of MSCs, with multidirectional differentiation properties into adipocytes, osteoblasts, chondrocytes, and other lineages, which have been investigated by experimental studies in vitro or in vivo [20][21][22] . ASCs are routinely harvested by the enzymatic method and then expanded for several generations to sufficient quantity, with significant aging and a decline in multipotency as well as the destruction of the vascular matrix 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they are ideal candidates for use as vehicles for gene therapy 1 . Thus far, ECs have been isolated from various sources, such as from peripheral blood mononuclear cells 2 , bone marrow mononuclear cells 3 , cardiac progenitors 4 , adipose-derived stem cells 5 and umbilical cord blood 6 . However, ECs from these adult sources are reported to be difficult to identify, isolate and expand in culture 7 .…”
Section: Introductionmentioning
confidence: 99%